Effect of in-mould electromagnetic stirring on the flow, initial solidification and level fluctuation in a slab mould: a numerical simulation study. (9th August 2019) - Yin, Yanbin; Zhang, Jiongming; Wang, Bo; Dong, Qipeng
ABSTRACT: In-mould electromagnetic stirring (M-EMS) is a widely used technique during slab continuous casting. To investigate the effect of M-EMS on the flow and initial solidification in a slab mould, a three-dimensional model coupling electromagnetic field, flow and solidification was developed. To track the steel/slag interface, the volume of fraction (VOF) model was coupled in the model. The electromagnetic force presents a centrally symmetrical distribution on the cross-section. The influences of stirring current and stirrer position on flow, initial solidification and level fluctuation have been discussed. M-EMS enhances the transversal flow and shrinks the lower recirculation in mould. The results indicate that both a higher stirring current and a lower stirrer position produce a reduction of the temperature in the mould centre. Furthermore, a higher stirrer position and a lower stirring current are favourable to the solidified shell growth. However, M-EMS aggravates the level fluctuation, which may lead to slag entrainment.